Isotope metrics refine herbivory among three nominally herbivorous reef fishes of socio-ecological importance - Joshua Pi; Stephane Martinez; Dana T. Cook; Milo Tasopulu; John Rulmal; Michelle J. Paddack; Nicole L. Crane; Giacomo Bernardi; Jonathan D. Cybulski; Kelton W. McMahon (Coral Reefs, 2026)
Herbivorous coral reef fishes are often assigned to different functional groups based on feeding mode and presumed ecosystem processes, such as algal removal ( i.e. , functional herbivory). However, these functional assignments do not necessarily identify assimilated resources nor predict nutritional pathways supporting fish biomass. We used stable carbon and nitrogen isotopes of amino acids to refine our understanding of herbivory among three nominally herbivorous fishes: Chlorurus spilurus , Ctenochaetus striatus , and Naso lituratus . Amino acid carbon isotope fingerprinting indicated much higher and more variable algal carbon contribution for N. lituratus (52.0% [22.0–84.1]) than C. spilurus (5.4% [0.9–17.8]) or C. striatus (4.8% [0.8–15.6]), which were corroborated by low trophic transfer values of N. lituratus ( Δδ 15 N Glu-Lys = 6.0 ± 0.9‰), high source δ 15 N Lys values (4.7 ± 1.0‰), and low microbial reworking ΣV values (0.9 ± 0.2). Conversely, higher Δδ 15 N Glu-Lys values of C. spilurus (7.9 ± 0.9‰) and C. striatus (9.0 ± 1.1‰) coupled with low δ 15 N Lys values (3.6 ± 1.0‰; 3.6 ± 1.1‰, respectively) and higher ΣV values (1.4 ± 0.2; 1.3 ± 0.2, respectively) indicated increased reliance on heterotrophically recycled production ( e.g. , bacteria, detritus, sponge tissue, mucus). Taken together, these data indicate N. lituratus as the most algivorous among our study species, while its broad source credible intervals may reflect epibiont assimilation, algal source variability, or intraspecific dietary variation. By linking carbon source assimilation and trophic transfer at the molecular level, we show that functionally “herbivorous” fishes can occupy distinct nutritional niches and that nutritional and functional definitions of herbivory may not always align.

The Marsupial Database: A comprehensive dataset on the ecology and life history of American and Australasian marsupials - Mariana Silva Ferreira; Rodrigo C. Rossi; Stephane Batista; Kathleen Sena; Kevin R. Bairos‐Novak; Shamia Farhana Shoma; Natália O. Leiner; Diego Astúa; Graeme Coulson; Diana O. Fisher; Natasha D. Harrison; Julian Nicholas Garcia Willmer; et al. (Ecology, 2026)
Marsupials are an important but typically neglected group of mammals that have been overlooked in many comparative analyses of vertebrate ecology and life history evolution. In order to address this knowledge bias, we have developed The Marsupial Database. The Marsupial Database contains traits for a phylogenetically diverse set of 414 extant and recently extinct (last 200 years) species from all seven modern marsupial orders (Dasyuromorphia, Didelphimorphia, Diprotodontia, Microbiotheria, Notoryctemorphia, Paucituberculata, Peramelemorphia) native to 34 countries in the Americas and Australasia. The database comprises 11,054 records of 35 traits describing anatomical, physiological, phenological, and reproductive characteristics, as well as information on species' ecology and current conservation status. Data were collected from 41 sources, comprising published databases and other relevant sources of information. By providing a centralized repository of marsupial ecological and life history traits, The Marsupial Database facilitates analyses of ecological and evolutionary patterns within the group, and also encourages inclusion of marsupials in comparative studies of mammals, vertebrates, and the entire animal kingdom. The Marsupial Database is free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Corrigendum to “Phenotypic diversity of brown trout (Salmo trutta L.) during the late Upper Pleistocene and Early Holocene in the glacial refugium of Iberia” [Palaeogeography, Palaeoclimatology, Palaeoecology (2025) 113073] - Ambra D'Aurelio; Lucía Agudo Pérez; Lawrence G. Straus; Manuel R. González Morales; Arturo Morales-Muñiz; Jerome Primault; Jean-Marc Roussel; Laurence Tissot; Stephane Glise; Frederic Lange; Camille Riquier; Michel Barbaza; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Phenotypic diversity of brown trout (Salmo trutta L.) during the late Upper Pleistocene and Early Holocene in the glacial refugium of Iberia - Ambra D'Aurelio; Lucía Agudo Pérez; Lawrence G. Straus; Manuel R. González Morales; Arturo Morales-Muñiz; Jerome Primault; Jean-Marc Roussel; Laurence Tissot; Stephane Glise; Frederic Lange; Camille Riquier; Michel Barbaza; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A Review of Elite Athlete Evidence-Based Knowledge and Preparation for Competing in the Heat - Chris J. Esh; Sarah Carter; Natalia Galan-Lopez; Frederic Garrandes; Stephane Bermon; Paolo Emilio Adami; Sebastien Racinais; Lewis James; Trent Stellingwerff; William M. Adams; Bryna Chrismas; Christopher J. Stevens; et al. (Journal of Science in Sport and Exercise, 2024)
Elite athletes will compete in extreme heat more frequently as global land and sea temperatures increase, alongside more intense, frequent and longer duration heatwaves. Best practices to protect athlete health and performance during competition include heat acclimation/acclimatisation [(HA); i.e., long-term pre-competition preparation] complemented by pre-planned and practised cooling and hydration strategies (i.e., short-term interventions immediately before or during competition). This review explores elite athletes’ current behaviours and practices when preparing for competition in the heat and assesses the level of knowledge that has been exhibited by athletes and their practitioners in this space. Recommendations for future research, discussions of current best practices, and methods to improve translation of research into practice are provided. Available research focuses on small samples of elite endurance athletes during a selection of World Championship/Olympic/Paralympic events (~6% of competing athletes). While generally an increase in the adoption of evidence-based HA is seen chronologically from 2015 onwards, universal adoption is not seen. HA adoption is lowest in those who live/train in cold/temperate environments with cost and access to facilities/equipment being the most commonly reported barriers. Further research is required across the sporting landscape to fully characterise elite athlete behaviours and practices in these spaces. International federations and national governing bodies should continue their efforts to educate athletes and focus on regularly updated and reinvigorated release of evidence-based guidelines (in multiple germane languages) for competing in the heat, to increase the adoption of HA and other heat related best practice.

Redefining North Atlantic right whale habitat‐use patterns under climate change - Erin L. Meyer‐Gutbrod; Kimberley T. A. Davies; Catherine L. Johnson; Stephane Plourde; Kevin A. Sorochan; Robert D. Kenney; Christian Ramp; Jean‐Francois Gosselin; Jack W. Lawson; Charles H. Greene (Limnology and Oceanography, 2023)
Changes in the physical oceanography of the Northwest Atlantic stemming from both natural and anthropogenic climate change impact the foraging ecology and distribution of endangered North Atlantic right whales. In this study, right whale sightings from 1990 to 2018 were analyzed to examine decadal patterns in monthly habitat use in 12 high‐use areas. Depth‐integrated abundances of late‐stage Calanus finmarchicus and Calanus hyperboreus were also analyzed for decadal variations in the right whale foraging habitats. There were significant differences in the occurrence, seasonal timing, and persistence of foraging habitats across these three decades. In the decades of the 1990s and the 2010s, prey was less abundant than in the 2000s, corresponding to reduced use of the Southeast US calving grounds in the winter, increased use of Cape Cod Bay in winter and spring, and reduced use of Roseway Basin in the fall. In the 2010s, right whale sightings increased in Southern New England and the Gulf of St. Lawrence in the spring and summer, respectively. Summertime declines in the 2010s in late‐stage copepod abundances in the Gulf of Maine and surrounding regions, as well as in the Gulf of St. Lawrence, indicate that recent increased use of the Gulf of St. Lawrence is driven by a decline in prey in traditional foraging habitats rather than by an increase in prey in the new foraging habitat. This analysis of decadal‐scale differences in right whale sightings and prey abundance is critical for redefining right whale distribution patterns for the most recent (post‐2010) decade.

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

Eighty Years of Mycopathologia: A Retrospective Analysis of Progress Made in Understanding Human and Animal Fungal Pathogens - Vishnu Chaturvedi; Jean-Philippe Bouchara; Ferry Hagen; Ana Alastruey-Izquierdo; Hamid Badali; Anamelia Lorenzetti Bocca; Jose F. Cano-Lira; Cunwei Cao; Sudha Chaturvedi; Sanjay H. Chotirmall; Anne D. van Diepeningen; Jean-Pierre Gangneux; et al. (Mycopathologia, 2018)

Climate warming alters the structure of farmland tritrophic ecological networks and reduces crop yield - Stephane A. P. Derocles; David H. Lunt; Sophie C. F. Berthe; Paul C. Nichols; Ellen D. Moss; Darren M. Evans (Molecular Ecology, 2018)
It is unclear how sustained increases in temperature and changes in precipitation, as a result of climate change, will affect crops and their interactions with agricultural weeds, insect pests and predators, due to the difficulties in quantifying changes in such complex relationships. We simulated the combined effects of increasing temperature (by an average of 1.4°C over a growing season) and applying additional rainwater (10% of the monthly mean added weekly, 40% total) using a replicated, randomized block experiment within a wheat crop. We examined how this affected the structure of 24 quantitative replicate plant–aphid–parasitoid networks constructed using DNA ‐based methods. Simulated climate warming affected species richness, significantly altered consumer–resource asymmetries and reduced network complexity. Increased temperature induced an aphid outbreak, but the parasitism rates of aphids by parasitoid wasps remained unchanged. It also drove changes in the crop, altering in particular the phenology of the wheat as well as its quality (i.e., fewer, lighter seeds). We discuss the importance of considering the wider impacts of climate change on interacting species across trophic levels in agroecosystems.

Collagens and proteoglycans of the cornea: importance in transparency and visual disorders - Dawiyat Massoudi; Francois Malecaze; Stephane D. Galiacy (Cell and Tissue Research, 2016)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The Chlamydomonas reinhardtii proteins Ccp1 and Ccp2 are required for long-term growth, but are not necessary for efficient photosynthesis, in a low-CO2 environment - Steve V. Pollock; Davey L. Prout; Ashley C. Godfrey; Stephane D. Lemaire; James V. Moroney (Plant Molecular Biology, 2004)

Surprisingly minor influence of TRAV11 (Vα14) polymorphism on NK T-receptor mCD1/α-galactosylceramide binding kinetics - Bee-Cheng Sim; Kaisa Holmberg; Stephane Sidobre; Olga Naidenko; Nathalie Niederberger; Shane D. Marine; Mitchell Kronenberg; Nicholas R. J. Gascoigne (Immunogenetics, 2003)

Combined effects of okadaic acid and cadmium on lipid peroxidation and DNA bases modifications (m 5 dC and 8-(OH)-dG) in Caco-2 cells - Adama Traoré; Stephane Ruiz; Isabelle Baudrimont; Ambaliou Sanni; Sébastien D. Dano; Ph. Guarigues; Jean François Narbonne; Edmond E. Creppy (Archives of Toxicology, 2000)